Fatigue failure load of monolithic Y-TZP three-unit-fixed dental prostheses: Effect of grinding at the gingival zone of the connector - Amaral, Marina (2017)
Objectives: To determine the fatigue failure loads of three-unit monolithic zirconia fixed dental prosthesis (FDPs) before and after grinding of the gingival areas of connectors with diamond burs. Material and methods: FDPs were milled from pre-sintered blocks of zirconia simulating the absence of the first mandibular molar. Half of the specimens were subjected to grinding, simulating clinical adjustment, and all of them were subjected to glazing procedure. Additional specimens were manufactured for roughness analysis. FDPs were adhesively cemented onto glass-fiber reinforced epoxy resin abutments. Fatigue failure loads and standard deviations were obtained using a staircase fatigue method (n=20, 100,000 loading cycles/5Hz). The initial test load was 70% of the mean load-to-fracture (n=3) and load increments were 5% of the initial test load for both the control and ground specimens. Data were compared by Student's T-test (a <= 0.05). Results: Both the control and ground groups exhibited similar values of load-to-fracture and fatigue failure loads. Neither the surface treatments nor ageing affected the surface roughness of the specimens. Conclusions: The damage induced by grinding with fine-grit diamond bur in the gingival area of the connectors did not decrease the fatigue failure load of the three-unit monolithic zirconia FDP.